Rewiring Recovery by Vagus Nerve Stimulation as a Durable Therapy for Post-Stroke Upper Limb Impairment - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Stroke remains a leading cause of long-term disability worldwide, with persistent Upper Extremity (UE) impairment affecting a significant proportion of survivors and posing a major challenge to functional recovery and quality of life. Conventional rehabilitation approaches, including physical and occupational therapy, Constraint-Induced Movement Therapy (CIMT), and neuromodulatory adjuncts, offer modest gains, particularly when initiated early. However, these benefits often plateau in the chronic phase, leaving many patients with enduring deficits. The VNS-REHAB trial marks a pivotal advancement in post-stroke rehabilitation by pairing Vagus Nerve Stimulation (VNS) with task-specific motor training. Unlike traditional uses of VNS in epilepsy and depression where stimulation is continuous or intermittent, this approach delivers VNS in a time-locked manner during rehabilitation, enhancing neuroplasticity and motor relearning. Clinical outcomes from this randomized controlled trial demonstrate not only significant improvements in motor function but also durable, patient-relevant gains persisting for at least one year. The success of this intervention reflects a broader evolution of VNS as a neuromodulatory tool, with expanding applications in epilepsy, treatment-resistant depression, migraine, inflammatory disorders, and cognitive dysfunction. Mechanistically, VNS engages central monoaminergic pathways, modulates cortical excitability, reduces inflammation, and amplifies experience-dependent plasticity, positioning it as a potent plasticity-enhancing adjunct in neurorehabilitation. While surgical implantation and patient selection pose challenges, the findings redefine the scope of recovery in chronic stroke, offering renewed hope for meaningful functional restoration long after injury.
Keywords: Vagus Nerve Stimulation; Stroke Rehabilitation; Upper Extremity Impairment; Neuroplasticity; Neuromodulation